VD_FINDINFO HC / 2013 / 262 vom 7. Mai 2013 - VD Tribunal cantonal (2013)
PROTECTION CONTRE LES CONGÉS, ÉGALITÉ ENTRE HOMME ET FEMME, CONGÉ DE REPRÉSAILLES | 336 al. 1 let. d CO, 3 LEg, 4 LEg, 5 al. 3 LEg, 6 LEg